Extraction, Purification, Physicochemical Properties, and Activity of a New Polysaccharide From Cordyceps cicadae - Tang, Zizhong; Lin, Wenjie; Chen, Yusheng; Feng, Shiling; Qin, Yihan; Xiao, Yirong; Chen, Hong; Liu, Yuntao; Chen, Hui; Bu, Tongliang; Li, Qinfeng; Cai, Yi; et al. (Frontiers in Nutrition, 2022)
The polysaccharides from C. cicadae were extracted by ultrasonically-assisted enzymatic extraction (UAEE). Response surface analysis was used to determine the optimum parameters as follows: addition of enzymes, 0.71%; extraction temperature, 60 °C; extraction time, 18 min; liquid-solid ratio, 46:1 (mL/g). The extraction yield of polysaccharide was 3.66 ± 0.87%. A novel polysaccharide fraction (JCH-a1) from C. cicadae was extracted and then purified by cellulose DEAE-32 and Sephadex G-100 anion exchange chromatography. The analysis results showed that the molar ratio of galactose, glucose, and mannose in JCH-a1 cells (60.7 kDa) was 0.89:1:0.39. JCH-a1 with a triple helix contains more α-glycosides and has strong thermal stability. Moreover, JCH-a1 showed strong antioxidant activity and acted as a strong inhibitor of α-glucosidase in vitro. In addition, JCH-a1 can prolong the lifespan of C. elegans. The present study might provide a basis for further study of JCH-a1 as an antioxidant and hypoglycaemic food or drug.